Code-Switching and Social Media in Bangladesh: Emergence of a New English - Kaniz Anjum Aorny; Md. Nazmul Haque; Md. Mozaffor Hossain (Linguistics Initiative, 2022)
Using two or more languages in a singular context or conversation is similar to going with the flow these days, specifically on social sites. This is referred to as "code-switching" by sociolinguists. The study aims at finding out the ratio and scenario of code-switching on social media in Bangladesh, and whether a New English has emerged or not for that. The study was conducted on a randomly chosen sample population of 40 participants across the country. It applied a mixed-method approach consisting of both qualitative and quantitative research methods to conduct this study. The study collected data through a close-ended questionnaire sent to the sample population via email, Messenger, WhatsApp, and Google Docs and some relevant data in the form of screenshots from Facebook posts, comments, and messenger chats. The findings of the study show that more than half of the participants in this research does not have the proper knowledge and intention regarding code-switching, and they perform it for sheer convenience in colloquial practice and communication. However, most of the participants do not support code-switching because they are concerned about their English language efficiency. And they also assert that Code-switching does not play a major role in the emergence of new sorts of English language because there are, in truth, other reasons behind this.